Determinants of Mortality in Patients with Nosocomial Acinetobacter baumannii Bacteremia in Southwest China: A Five-Year Case-Control Study - Shuangshuang Yang; Jide Sun; Xianan Wu; Liping Zhang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Purpose. This study was aimed to identify the determinants of in-hospital mortality in Acinetobacter baumannii (A. baumannii) bacteremia and to assess impact of carbapenem resistance on mortality. Methods. A five-year case-control study was conducted from January 2011 to December 2015 in a tertiary teaching hospital with 3200 beds, Southwest China. Clinical outcomes and potential determinants of mortality in patients with nosocomial A. baumannii bacteremia and carbapenem-resistant A. baumannii (CRAB) bacteremia were evaluated using Cox and logistic regression analyses. Results. A total of 118 patients with nosocomial A. baumannii bacteremia were included. Seventy-one percent (84/118) of them had carbapenem-resistant A. baumannii (CRAB) bacteremia. The in-hospital mortality of nosocomial A. baumannii bacteremia was 21.2%, and the attributable in-hospital mortality rate due to CRAB was 21.5%. Significant difference of 30-day in-hospital mortality in the Kaplan–Meier curves was found between CRAB and CSAB groups (log-rank test, P=0.025). The Cox regression analysis showed that patients with CRAB bacteremia had 2.72 times higher risk for 30-day in-hospital mortality than did those with carbapenem-susceptible A. baumannii (CSAB) bacteremia (95% confidence intervals (CIs) 1.14–6.61, P=0.016). The logistic regression analysis reported that mechanical ventilation and respiratory tract as origin of bacteremia were independent predictors of mortality among patients with nosocomial A. baumannii bacteremia and CRAB bacteremia, while high APACHE II score on the day of bacteremia and multiple organ dysfunction syndromes (MODS) during hospitalization were independent predictors of mortality among patients with nosocomial A. baumannii bacteremia but not CRAB bacteremia. Conclusion. It was the severity of illness (high APACHE II score and MODS) not carbapenem resistance that highlighted the mortality of patients with nosocomial A. baumannii bacteremia. The impact of mechanical ventilation on mortality suggested that respiratory dysfunction might prime the poor outcome. Protection of respiratory function during the progression of nosocomial A. baumannii bacteremia should be given more importance. Early identification and intervention of patients with nosocomial A. baumannii bacteremia in critical ill conditions were advocated.